TEXTURAL AND CHEMICAL VARIATION IN PLAGIOCLASE PHENOCRYSTS FROM THE 1980 ERUPTIONS OF MOUNT ST. HELENS, USA - Berlo K.; Blundy J.; Hawkesworth C.; Turner S. (My University, 2007)
This study presents major- and trace-element chemistry of plagioclase phenocrysts from the 1980 eruptions of Mount St. Helens volcano. Despite the considerable variation in textures and composition of plagioclase phenocrysts, distinct segments have been cross-correlated between crystals. The variation of Sr and Ba concentration in the melt, as calculated from the concentration in the phenocrysts using partition coefficients, suggests the cores and rims crystallised from compositionally different melts offset by the plagioclase crystallisation vector. In both of these melts Sr and Ba are correlated despite the abundance of plagioclase in the 1980 dacites. We propose that rapid crystallisation of plagioclase upon magma ascent caused a shift in melt composition towards lower Sr and higher Ba, as documented in the rims of the phenocrysts. Although the cores of the phenocrysts crystallised at relatively shallow depths, they preserve the Sr and Ba of the deep-seated melts as they ascended from a deeper region. Further magma ascent resulted in microlite nucleation, which is responsible for a similar shift to even lower Sr concentration as observed in the groundmass of post-18 May 1980 samples. © Springer-Verlag 2007.
Keywords: CRYSTALLISATION; MOUNT ST. HELENS; NUCLEATION; PLAGIOCLASE; SR AND BA